Optimization of costs of logistics activities of the enterprise - Wei, Yin (Харківський національний автомобільно-дорожній університет, 2024)
The thesis improves the methodological foundations for selecting the processes of the enterprise's logistics activities and further develops the system of management of the enterprise's logistics processes. It is proposed to introduce a controlling service at the enterprise, the introduction of which will help to stabilize and strengthen the strategic position of the enterprise in the national market, as well as determine the flexibility of the enterprise's response to the impact of external factors Forecast assumptions about the development of the object of study – the formation of a system for managing logistics processes at an enterprise, taking into account the introduction of a controlling service.
Keywords: logistics; logistics system; processes; formation; logistics processes of the enterprise; controlling